2016
DOI: 10.1099/jgv.0.000574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the live-attenuated Japanese encephalitis vaccine SA14 -14-2 strain with its pre-attenuated virulent parent SA14 strain: similarities and differences in vitro and in vivo

Abstract: Japanese encephalitis virus (JEV) is the main cause of acute viral encephalitis, primarily affecting children and young adults in the Asia-Pacific region. JEV is a vaccine-preventable pathogen, with four types of JE vaccine licensed in different regions of the world. To date, the most common JEV strain used in vaccine development and production is SA14-14-2, an attenuated strain derived from its wild-type parental strain SA14. In this study, we directly compared the phenotypic and genotypic characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 54 publications
4
41
1
Order By: Relevance
“…The latter safety result is impressive because I.C. inoculation with YFV 17D and JEV SA14–14-2 (two licensed live-attenuated flavivirus vaccines) results in lethal disease in one-day-old newborn mice 21,22 . Although potential homologous recombination between the WT and vaccine ZIKVs might pose a safety liability for the 10-del vaccine candidate, it should be noted that recombination events are rare and could not be detected in cell culture 23–27 .…”
mentioning
confidence: 99%
“…The latter safety result is impressive because I.C. inoculation with YFV 17D and JEV SA14–14-2 (two licensed live-attenuated flavivirus vaccines) results in lethal disease in one-day-old newborn mice 21,22 . Although potential homologous recombination between the WT and vaccine ZIKVs might pose a safety liability for the 10-del vaccine candidate, it should be noted that recombination events are rare and could not be detected in cell culture 23–27 .…”
mentioning
confidence: 99%
“…82 Compared to the wild-type SA14 virus, the SA14-14-2 LAV shows a slight growth defect (smaller plaque size, slower kinetics, lower titres) in BHK-21 cells, and is highly attenuated for neuroinvasion and neurovirulence in ICR mice. 83 The LAV fails to replicate in mosquitoes when fed through a blood meal, while it replicates to low titres when inoculated intrathoracically in C. tritaeniorhynchus, but with an inability to be transmitted to suckling mice, 82 suggesting that the SA14-14-2 LAV is transmission-incompetent. The LAV strain has also been shown to be stable upon passage in mosquito or mammalian cells in vitro, or in mice (both intracerebral and intraperitoneal) or mosquitoes.…”
Section: Live Attenuated Virus (Lav) Vaccinesmentioning
confidence: 99%
“…A seminal study showed that multiple (at least 4) mutations in the E protein are required for attenuation of neurovirulence, 98 although other studies have shown that a single mutation in the C protein (S66L), or an additional mutation in the E protein (G244E) may also lead to attenuation without loss of immunogenicity in mice. 95,99 Recent studies have also shown that the SA14-14-2 LAV is unable to produce the NS1 0 protein due to the loss of the RNA pseudoknot structure as a result of a single point mutation (G66A) in the NS2A coding region, 83,100 although this does not appear to significantly affect neurovirulence. 101 Despite the excellent safety record of SA14-14-2 LAV vaccine, 102 some issues have been raised about its regulatory compliance.…”
Section: Live Attenuated Virus (Lav) Vaccinesmentioning
confidence: 99%
“…In contrast to virulent JEV strains as RP9, the vaccine strain SA14-14-2 was shown to be essentially non-neuroinvasive and non-neurovirulent in weanling ICR mice, but is still highly neurovirulent in neonates [16]. JEV SA14-14-2 genome displays 57 nucleotide differences positioned along the genome when compared to the parental strain SA14, leading to 25 amino-acid substitutions [16].…”
Section: Introductionmentioning
confidence: 99%